An Investigation of the Effects of Knowledge Management and Technological Innovations on the Creation of Competitive Advantage (Case study: Pars Khazar and Pars Shahab Manufacturing Companies) - Naser Seifollahi; Hatef Hazeri; Ali Asoudeh (مدیریت راهبردی دانش سازمانی, 2019)
This research is aimed at investigating the effects of knowledge management and technological innovation on the creation of competitive advantage in Pars Khazar and Pars Shahab manufacturing  companies .  The statistical population of the study consisted of 280 the managers and experts of Pars Khazar and Pars Shahab Manufacturing Companies from whom 123 were selected as the sample by Cochran formula by cluster sampling method. Field survey is used for data collection, and a standardized questionnaire was employed as data collection tool. Tabarsa and Ahmadvand’s questionnaire  (2017) was used for knowledge management, Camison & Villar-Lopez’s questionnaire (2014) was used for measuring the technological innovation, and Hill and Jones (2003) questionnaire was used for measuring the competitive advantage variable. Structural equation modeling test using Smart PLS2 software was employed to test the research hypotheses. The results specified that two main independent variables, namely knowledge management (coefficient: 39) and technological innovation (coefficient: 55) significantly affected the dependent variable of competitive advantage in the companies. Moreover, knowledge management turned out to have a significant effect on technological innovation (coefficient: 65) through technological innovation to have a significant effect on creating competitive advantage (coefficient: 36) in the companies. Furthermore, the criteria for measuring the model fitness, including R2 and Q2, confirmed its fitness.